2018
DOI: 10.1155/2018/5076269
|View full text |Cite
|
Sign up to set email alerts
|

DCE-MRI Pharmacokinetic-Based Phenotyping of Invasive Ductal Carcinoma: A Radiomic Study for Prediction of Histological Outcomes

Abstract: Breast cancer is a disease affecting an increasing number of women worldwide. Several efforts have been made in the last years to identify imaging biomarker and to develop noninvasive diagnostic tools for breast tumor characterization and monitoring, which could help in patients' stratification, outcome prediction, and treatment personalization. In particular, radiomic approaches have paved the way to the study of the cancer imaging phenotypes. In this work, a group of 49 patients with diagnosis of invasive du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 75 publications
1
45
1
Order By: Relevance
“…Recently, several articles have outlined the potential clinical applicability of radiomics in the field of breast cancer for different purposes, e.g. diagnosis 10 , 11 , tumor response prediction 12 14 , prediction of molecular tumor subtype 15 , 16 , and prediction of axillary lymph node metastases 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several articles have outlined the potential clinical applicability of radiomics in the field of breast cancer for different purposes, e.g. diagnosis 10 , 11 , tumor response prediction 12 14 , prediction of molecular tumor subtype 15 , 16 , and prediction of axillary lymph node metastases 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…This technique is multi-parametric and allows for several observations, both morphological and based on tumor contrast kinetics. Several studies using this technique showed a correlation between molecular subtypes and qualitative and semi-quantitative tumor features [ 24 , 35 , 36 ] and between perfusion parameters [ 37 ] and semi-automatic features of the images [ 9 , 22 , 38 , 39 , 40 , 41 , 42 , 43 ] after fusion imaging [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further work is required to assess the combined information from DCE‐MRI, DW‐MRI and PET, together with biological/histological data, in order to conduct an advanced analysis in a radiogenomic framework …”
Section: Discussionmentioning
confidence: 99%